Perceptions on implementation of Automotive National Diploma Curriculum on its Trainees’ Preparation for Job Performance of Technical Vocational Education Training (Tvet) in Nairobi Region - Mwangi, S. Wokabi (Advances in Social Sciences Research Journal, 2015)
This paper examines the perceptions on implementation of automotive national Diploma curriculum on its trainee’s preparation for job performance. The paper will explore the historical development of Technical Vocational Education and Training which can be traced back to the pre-colonial days. The origins of the testing and certification of technical skills in Kenya (Trade Testing System) will be explored, the challenges of the automotive technician today due to fast changes of technology and highlight of the beneficiaries of the research findings. Technical Vocational Education Training (TVET) has been viewed differently both from policy and implementation viewpoints. For instance, the Australian Council for Education and Research argues that, training is a basic tool that can enhance employability among the long-term unemployed, enhances social networks and employer based programmes. At the same time it appears that concentrating on more fundamental attitude building and personal development can have an additional far-reaching effect as well as focusing on assertiveness, self-esteem, self-efficacy and confidence. Training if successful could have huge implications for reducing unemployment and maintaining employability (report by Australian Chamber and Industry, 2001). The African Union (AU) also, has a vision of “an integrated, peaceful, prosperous Africa, driven by its own people to take its rightful place in the global community and the knowledge economy.” This vision is predicts on the development of the continent’s human resources. In its Plan of Action for the Second Decade of Education (2006 – 2015), the AU recognizes the importance of TVET as a means of empowering individuals to take control of their lives and recommends therefore the integration of vocational training into the general education system. Kenya in its attempt to realize the AU vision and in ensuring the provision of training opportunity to all its citizens therefore, did a rapid appraisal on the status of Technical and Vocational Education and Training (TVET) in September, 2003.It is within this framework that the Kenyan government developed a National Training Strategy (NTS) to revitalize the sector. NTS policy document outlines strategic direction focusing on the future development and aspirations of TVET in Kenya. This study concluded that the entry Mean Grade of the students for this course was fair C-. However, the results of KCSE cluster subjects needed as a strong foundation for pursuing the engineering based courses were not considered as pre requisite for admission to the diploma course which could be a contributing factor of trainees’ poor preparation for job performance at the work place. This paper recommends that the ministry responsible for TVET sector in collaboration with all stakeholders in Education and training should come up the policy guidelines on the minimum entry grades to include cluster subjects. The Current position of entry requirement without cluster of the prerequisite subject may allow trainees cope up with the curriculum content .Thus, need to review the entry requirements for automotive diploma training programme.